Spatiotemporal evolution of 1998 extreme flood event in the Yangtze River basin from the perspective of the reconstructed GRACE/GRACE-FO data - Lilu Cui; Jiacheng Meng; Bo Zhong; Jiachun An; Yu Li; Haoyang Guo; Yuheng Lu (Journal of Hydrology: Regional Studies)
Study region: Yangtze River basin (YRB), China Study focus: The primary objective of this study is to reconstruct GRACE (Gravity Recovery and Climate Experiment) data from 1992 to 2002 and assess the 1998 extreme floods in the YRB. To achieve this, we developed an improved reconstruction algorithm that incorporates regional differences in the relationships between terrestrial water storage changes (TWSC) and hydrometeorological variables, thereby enhancing the accuracy of the reconstructed results. We also analyzed the development and propagation of the flood, as well as the deep connections between the flood and the El Niño event. New hydrological insights for the region: This study provides a new idea for the GRACE reconstruction data, revealing the importance of accurately determining the key input hydrometeorological elements for the reconstruction model. This offers certain reference for studying the regional differences in the relationship between hydrometeorological elements and TWSC. Key findings: Include compared with traditional algorithm, the reconstruction results based on our algorithm have significantly improved when compared with the water balance and hydrological models. Specifically, the root-mean-square error (RMSE) was reduced by 48.09 % and 27.14 % compared to the WB and GLDAS results, respectively. The 1998 extreme flood occurred between June and September, with cumulative TWSC exceeding normal levels by 55.62 billion tons. The extreme flood was primarily caused by elevated terrestrial water storage due to prior precipitation (PRE), further exacerbated by heavy PRE, which was linked to the strong 1997 El Niño event. Additionally, human activities played a contributing role in intensifying the flood.